2016
DOI: 10.1093/geronb/gbw030
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Medicare Part D on Health Outcomes of Newly Covered Medicare Beneficiaries

Abstract: Part D has had a sustained impact on cost-related nonadherence rates and the health status of newly covered beneficiaries. However, the change in health status is conditional on remaining enrolled in a Part D plan over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Yin et al (2008) estimated a slightly smaller reduction in out-of-pocket prescription expenditures of almost 13% while increasing utilization by nearly 6%. By reducing the cost of prescription medication, Part D has reduced cost-related prescription nonadherence, which likely accounts for some of the health improvements linked to the program (Diebold, 2016; Kennedy, Maciejewski, Liu, & Blodgett, 2011). Afendulis, He, Zaslavsky, and Chernew (2011) show that Part D reduced the likelihood of Medicare beneficiaries being hospitalized for congestive heart failure by 6.4%, diabetes by 15.5%, and asthma by 12.1%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin et al (2008) estimated a slightly smaller reduction in out-of-pocket prescription expenditures of almost 13% while increasing utilization by nearly 6%. By reducing the cost of prescription medication, Part D has reduced cost-related prescription nonadherence, which likely accounts for some of the health improvements linked to the program (Diebold, 2016; Kennedy, Maciejewski, Liu, & Blodgett, 2011). Afendulis, He, Zaslavsky, and Chernew (2011) show that Part D reduced the likelihood of Medicare beneficiaries being hospitalized for congestive heart failure by 6.4%, diabetes by 15.5%, and asthma by 12.1%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A related study by Kaestner, Long, and Alexander (2014) indicates that Part D reduced hospital admissions for congestive heart failure by 18%, coronary artery disease by 13%, and chronic obstructive pulmonary disorder by 32%. Most recently, Diebold (2016) shows that Part D improved the self-reported health status of newly covered beneficiaries and reduced the likelihood that this group is diagnosed with high blood pressure. Poor health status and chronic health conditions are associated with work impairments that result in a higher likelihood of labor force exits and a reduced likelihood of reentry (Blau & Gilleskie, 2001; Mutchler, Burr, Massagli, & Pienta, 1999; Sammartino, 1987; Zissimopoulos & Karoly, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the amount of out‐of‐pocket costs for drugs decreased substantially after the implementation of the program, although the total number of prescription drugs per patient increased (Liu et al., 2011; Yin et al., 2008). Furthermore, providing a greater level of access to drugs through insurance resulted in better health outcomes from both individual and community levels (Afendulis et al., 2011; Diebold, 2018). Despite these positive results, there still remain significant gaps in knowledge regarding the equity impact of Part D on inappropriate prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…This new prescription drug coverage program contributed to 18% reductions in out‐of‐pocket costs for prescription drugs among Medicare beneficiaries compared to 2005, and an increase of the percentage of the beneficiaries with any drug coverage up to 90% in 2006 (Hu et al., 2017; Lichtenberg & Sun, 2007). Additionally, in terms of an impact on health outcomes, the Part D program led to reduction of hospitalization rate as well as increased the likelihood of reporting good or better health among the beneficiaries (Afendulis et al., 2011; Diebold, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…10 A recent review of the effect of Medicare Part D concluded that, overall, Part D has increased medication use and reduced out-of-pocket medication costs for beneficiaries but that the effect on dually eligible beneficiaries may differ for different diseases. 11 Medicare Part D has been associated with reductions in cost-related medication nonadherence, emergency department visits, mortality, hospitalization disparities, and depressive symptoms, [12][13][14][15][16] although one study that evaluated costrelated medication nonadherence found no reduction in ethnoracial disparities after Part D. 17 Some older ethnoracial minority adults of low socioeconomic status may have difficulties navigating the Part D program. 18 Although the effects of Part D are often evaluated as starting in 2006, evidence suggests that the announcement of the program in December 2003 affected beneficiary and insurance company decisions in anticipation of the expected increase in coverage.…”
mentioning
confidence: 99%